Environment-friendly light building material

By using silicate cement, perlite, fly ash and other components in lightweight building materials, and adding fiber materials and foaming agents, the environmental protection, impact resistance and drying and shrinking problems of the material are solved, and higher stability and thermal insulation properties are achieved.

CN119822733APending Publication Date: 2025-04-15HEBEI SHENGDONG NEW MATERIALS CO LTD

Patent Information

Application Number
CN202510042189.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously improve the environmental protection, impact resistance and reduce deformation problems caused by drying and shrinkage of lightweight building materials.

Method used

Using a combination including silicate cement, perlite, fly ash, fiber materials, foaming agents, polyvinyl alcohol and polyacrylamide, the water diffusion path is improved through fiber materials, the foaming agent generates pore structure, and the polymer enhances bonding and water retention, and jointly improves the stability and impact resistance of the material.

Benefits of technology

It effectively suppresses the shrinkage and deformation of the material, improves the dimensional stability and impact resistance of the material, and reduces the density and drying shrinkage of the material, enhances environmental protection and thermal insulation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005237279320000081
    Figure BDA0005237279320000081
Patent Text Reader

Abstract

The invention discloses an environment-friendly light building material, and mainly relates to the technical field of Portland cement. Compared with the prior art, the environment-friendly light building material comprises Portland cement, perlite, fly ash, a fiber material, a foaming agent, polyvinyl alcohol, polyacrylamide and water, and the fiber material is one of sepiolite fibers, aluminum silicate fibers, wood fibers and modified wood fibers. By adding the fiber material, the phenomena of macropores, microcracks and the like caused by non-uniform drying shrinkage of the material are avoided, shrinkage difference caused by non-uniform water distribution is reduced, the internal humidity change of the material is alleviated, rapid volume shrinkage caused by rapid reduction of water is avoided, shrinkage deformation of the material is effectively inhibited, and the service life of the material is prolonged. Therefore, the dimensional stability of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mixtures containing concrete, and in particular to an environmentally friendly lightweight building material. Background Art

[0002] Building materials can be divided into structural materials, decorative materials, functional materials, etc. Structural materials mainly include wood, stone, cement, concrete, steel, etc. These materials are used for the load-bearing part of the building structure. For example, the frame, beams and columns of the building are mainly supported by structural materials to ensure the stability and safety of the building; decorative materials include coatings, wallpapers, ceramic tiles, decorative panels, etc., which are mainly used for the decoration of the interior and exterior walls and floors of the building, and play a role in beautifying the building and improving the indoor and outdoor environment; functional materials include materials with specific functions such as waterproofing, fire prevention, thermal insulation, etc. Lightweight materials refer to materials with low density, such as lightweight aggregate concrete, foamed concrete, etc. Lightweight materials are widely used in the construction field. In places where there are strict restrictions on the weight of the building, such as high-rise buildings and non-load-bearing parts of large-span buildings, lightweight materials can be used to reduce the weight of the building and reduce the foundation pressure.

[0003] In the field of construction engineering, a lower drying shrinkage rate can effectively prevent cracks or deformations caused by shrinkage in lightweight materials during use, which can not only maintain the integrity and stability of the building structure, reduce leakage problems caused by cracks, but also extend the service life of the building and reduce the cost of later maintenance. To reduce the drying shrinkage rate of lightweight materials, we can first optimize the material mix ratio, strictly control the water consumption in lightweight materials, and avoid the situation where the water-cement ratio is too large. Excessive water will lead to an increase in capillary pores, thereby increasing drying shrinkage. Additives that can improve the volume stability of lightweight materials can also be added to the components of lightweight materials. The production process can also be improved to ensure that the internal structure of the material is more uniform and dense, and the porosity is reduced. In terms of decoration and renovation, improving impact resistance can reduce material damage caused by minor collisions in daily use, maintain the durability and beauty of the decorative effect, and thus increase the service life of building materials. In the research and development and production of lightweight materials, we focus on using renewable resources or industrial waste as raw materials, such as using industrial waste such as fly ash to make foamed concrete, which not only solves the problem of waste disposal, but also realizes the recycling of resources, which is in line with the concept of green environmental protection.

[0004] CN103693900A discloses a lightweight material for construction and a preparation method thereof. The lightweight material for construction described in the invention is composed of a cementitious material, a reinforcing material, an aggregate, a composite foaming agent and a residual material, wherein the cementitious material is cement, the reinforcing material is a glass fiber mesh cloth, the aggregate is fly ash, slag and steel slag, the composite foaming agent is hydrogen peroxide and a foam stabilizer, the residual material is a water reducer, an early strength agent, a waterproofing agent, an activator and water, and according to a certain weight portion, a glass fiber mesh cloth is laid in a mold to prepare a slurry, and the slurry is poured into the mold where the glass fiber mesh cloth is laid, and finally the lightweight material for construction is obtained after defoaming, curing and curing. The invention uses fly ash, slag and steel slag as aggregates, turns a large amount of industrial waste into treasure, saves energy and is environmentally friendly, and greatly reduces production costs; the production process is simple and easy to operate, and the obtained product has excellent and stable performance.

[0005] CN116283158A discloses a lightweight, low-shrinkage, ultra-high performance concrete based on waste ceramics and a preparation method thereof. The invention uses waste porous ceramics as aggregates to prepare ultra-high performance concrete, which can not only save natural resources and turn waste into treasure, but also reduce environmental pollution, improve the ecological environment, and promote the sustainable development of the social economy; using perlite powder to replace part of cement and other cementitious materials can reduce the amount of cement, save resources and energy, and comply with the national sustainable development strategy. At the same time, it can improve the pore structure of the hardened cement paste and further reduce the dead weight of the concrete, while improving the compressive strength and reducing the drying shrinkage rate, and has good working performance, mechanical properties and volume stability.

[0006] The solutions reported in the above patent documents cannot solve the problems of impact resistance and deformation caused by drying shrinkage at the same time. Summary of the invention

[0007] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to improve the environmental protection and impact resistance of lightweight building materials, reduce drying shrinkage and thus reduce deformation caused by shrinkage.

[0008] To achieve the above object, the present invention provides an environmentally friendly lightweight building material, comprising the following components by weight: 15-20 parts of silicate cement, 15-25 parts of perlite, 15-25 parts of fly ash, 1-2 parts of fiber material, 0.6-1.0 parts of foaming agent, 2-6 parts of polyvinyl alcohol, 1-2 parts of polyacrylamide, and 40-60 parts of water. The fiber material is one of sepiolite fiber, aluminum silicate fiber, wood fiber, and modified wood fiber.

[0009] The foaming agent is sodium rosinate.

[0010] The preparation method of the modified wood fiber is as follows, in parts by weight:

[0011] 1.2-1.6 parts of propylene glycol, 0.4-0.8 parts of carbonate, 8-12 parts of water are added, ultrasonically dispersed, citric acid aqueous solution is added dropwise to adjust the pH, 1.2-1.6 parts of wood fiber is added thereto and soaked for 1-2 hours, and the filter cake is filtered and dried to obtain modified wood fiber.

[0012] The pH is adjusted to 7-8.

[0013] The carbonate is a mixture of one or more of magnesium carbonate, copper carbonate, calcium carbonate and zinc carbonate.

[0014] The citric acid aqueous solution is 10-20 wt%.

[0015] A method for preparing an environmentally friendly lightweight building material is as follows:

[0016] Portland cement, perlite, fly ash, fiber material, foaming agent, polyvinyl alcohol, polyacrylamide and water are mixed and stirred evenly to obtain slurry, which is poured into a mold, and the environmentally friendly lightweight building material is obtained after solidification and curing.

[0017] Portland cement is the main cementitious material in the lightweight building material of the present invention. After adding water, it undergoes a hydration reaction to form a gel product, which gradually hardens after being evenly mixed with other components and bonds other components together, giving the material strength and stability, ensuring that the material has good load-bearing capacity after solidification, and meeting the basic requirements of lightweight building structures for strength. In the entire material system, Portland cement plays a core role in building a skeleton and providing basic strength, and is a key factor in ensuring that the material can withstand external loads.

[0018] Perlite has the characteristics of being light and porous, and its rich internal pore structure makes it mainly play the role of reducing weight and improving thermal insulation performance in building materials. In the present invention, perlite can effectively reduce the overall density of the material, making the building material lighter, convenient for construction and transportation, while reducing the weight of the building itself, and having little impact on the load of the building structure. Its porosity can also hinder the transfer of heat, and when used in buildings, it helps to improve the thermal insulation effect, reduce energy consumption, and maintain indoor temperature stability; the particle shape of perlite can also increase the internal friction of the material, improve the material's anti-deformation ability to a certain extent, and work synergistically with other components to optimize the comprehensive performance of the material.

[0019] Fly ash is an industrial waste. Its use in the environmentally friendly lightweight building materials of the present invention realizes the resource utilization of waste. In terms of material performance, fly ash contains active ingredients that can participate in the reaction during cement hydration, further fill the pores inside the material, and refine the microstructure, thereby improving the density and strength of the material, making the material easier to operate during construction processes such as mixing and pouring, improving construction quality and efficiency, and cooperating with other components to jointly improve the performance of building materials.

[0020] Fiber material is an important component for improving the performance of environmentally friendly lightweight building materials. When drying occurs, water loss is free evaporation, which is prone to produce large pores and micro cracks. The addition of fiber material in the present invention can avoid the problem of uneven shrinkage caused by the formation of local concentration gradients of water during the drying and shrinkage of the material; by adding fiber material, the diffusion path of water in the material is improved to make it more uniform, the shrinkage difference caused by uneven water distribution is reduced, the humidity change inside the material is moderated, and the rapid shrinkage of the volume caused by the rapid reduction of water is avoided. At the same time, by bearing and dispersing stress, the generation and expansion of micro cracks are prevented, and the shrinkage and deformation of the material are effectively inhibited, thereby improving the dimensional stability of the material.

[0021] The foaming agent is responsible for producing the pore structure in environmentally friendly lightweight building materials. During the preparation process, the foaming agent reacts to produce gas, forming evenly distributed tiny pores, which can reduce the density of the material and make the material lighter. At the same time, the existence of pores can also absorb and buffer external impact forces and improve the seismic performance of the material. The pores produced by the foaming agent not only ensure the lightweight characteristics of the material, but also will not seriously weaken the strength of the material due to too many pores. It cooperates with other components to reduce the weight of the material while maintaining the basic mechanical properties of the material, meeting the requirements of the construction project for lightweight, seismic resistance and other properties.

[0022] Polyvinyl alcohol plays a major role in thickening and bonding in environmentally friendly lightweight building materials. It can increase the viscosity of the material, improve the rheological properties of the material, make the components more evenly mixed during the stirring process, prevent stratification and segregation, and ensure the uniformity and stability of the material. At the same time, polyvinyl alcohol has good bonding properties, which can enhance the bonding force between the components and improve the integrity of the material. It can effectively play these roles and work in synergy with other components to improve the construction performance and use performance of building materials, and ensure that the material has good structural integrity and stability after curing.

[0023] Polyacrylamide polymer is mainly used in environmentally friendly lightweight building materials to enhance the water retention and improve the dispersibility of materials. It can absorb a large amount of water to form a hydrogel, thereby slowing down the evaporation rate of water inside the material, maintaining the humidity of the material during construction and curing, and is conducive to the full hydration reaction of cementitious materials such as cement, thereby improving the strength and durability of the material. The functional groups on its molecular chain can interact with other components, promote the uniform dispersion of each component, avoid particle agglomeration, and improve the comprehensive performance of building materials.

[0024] Water can adjust the fluidity of environmentally friendly lightweight building materials, allowing them to be smoothly poured into the mold, filling every corner of the mold and ensuring the molding quality of the material. During the curing process of the material, the evaporation of water will affect the pore structure and performance of the material. Therefore, reasonable control of the amount of water is crucial to obtaining ideal material properties.

[0025] Beneficial effects of the present invention:

[0026] Compared with the prior art, the environmentally friendly lightweight building material of the present invention comprises silicate cement, perlite, fly ash, fiber material, foaming agent, polyvinyl alcohol, polyacrylamide, and water component, wherein the fiber material is one of sepiolite fiber, aluminum silicate fiber, wood fiber, and modified wood fiber. The fiber material is added to avoid the phenomenon of macropores and microcracks caused by uneven shrinkage of the material during drying, reduce the shrinkage difference caused by uneven water distribution, moderate the humidity change inside the material, avoid the sharp shrinkage of volume caused by the sharp reduction of water, effectively inhibit the shrinkage and deformation of the material, and thus improve the dimensional stability of the material. DETAILED DESCRIPTION

[0027] The parameters of the specific chemical substances used in the examples are from the following sources:

[0028] Perlite: 100 mesh, manufacturer is Tianmen Hengchang Chemical Co., Ltd., product number is HC8179.

[0029] Portland cement: The brand is Albion Portland, the grade is 525.

[0030] Fly ash: The manufacturer is Wuhan Jiyesheng Chemical Co., Ltd., and the product number is A01085.

[0031] Wood fiber: The manufacturer is Dacheng County Yi Bo Chemical Co., Ltd., and the item number is 213.

[0032] Sepiolite fiber: The manufacturer is Shijiazhuang Mayue Building Materials Co., Ltd., and the product number is MY-5.

[0033] Aluminum silicate fiber: The manufacturer is Lingshou County Yehui Mineral Products Co., Ltd., and the item number is 12-36.

[0034] Polyvinyl alcohol: molecular weight is 2400-2600, viscosity is 48.0-60.0 mPa·s, manufacturer is Wuhan Ruishengcheng Chemical Co., Ltd., item number is 22-99H.

[0035] Polyacrylamide: The manufacturer is Suzhou Haonuo Industry and Trade Co., Ltd., and the item number is 519.

[0036] Example 1

[0037] A method for preparing an environmentally friendly lightweight building material is as follows:

[0038] 18 kg of Portland cement, 20 kg of perlite, 20 kg of fly ash, 0.8 kg of sodium rosin acid, 4 kg of polyvinyl alcohol, 1.5 kg of polyacrylamide and 50 kg of water are mixed and stirred evenly to obtain slurry, which is poured into a mold, and the environmentally friendly lightweight building material is obtained after solidification and curing.

[0039] Example 2

[0040] A method for preparing an environmentally friendly lightweight building material is as follows:

[0041] 18 kg of Portland cement, 20 kg of perlite, 20 kg of fly ash, 1.5 kg of wood fiber, 0.8 kg of sodium rosin acid, 4 kg of polyvinyl alcohol, 1.5 kg of polyacrylamide, and 50 kg of water are mixed and stirred evenly to obtain slurry, which is poured into a mold, and the environmentally friendly lightweight building material is obtained after solidification and curing.

[0042] Example 3

[0043] A method for preparing an environmentally friendly lightweight building material is as follows:

[0044] 18 kg of silicate cement, 20 kg of perlite, 20 kg of fly ash, 1.5 kg of modified wood fiber, 0.8 kg of sodium rosin acid, 4 kg of polyvinyl alcohol, 1.5 kg of polyacrylamide, and 50 kg of water are mixed and stirred evenly to obtain slurry, which is poured into a mold, and the environmentally friendly lightweight building material is obtained after solidification and curing.

[0045] The preparation method of the modified wood fiber is as follows, in parts by weight:

[0046] 1.4 kg of propylene glycol, 0.3 kg of magnesium carbonate and 0.3 kg of zinc carbonate were added to 10 kg of water, and ultrasonically dispersed for 5 minutes. A 10 wt % aqueous solution of citric acid was added dropwise to adjust the pH to 7.5. 1.4 kg of wood fiber was added thereto and soaked for 1 hour. The filter cake was filtered and dried to obtain modified wood fiber.

[0047] Example 4

[0048] A method for preparing an environmentally friendly lightweight building material is as follows:

[0049] 18 kg of silicate cement, 20 kg of perlite, 20 kg of fly ash, 1.5 kg of sepiolite fiber, 0.8 kg of sodium rosin acid, 4 kg of polyvinyl alcohol, 1.5 kg of polyacrylamide and 50 kg of water are mixed and stirred evenly to obtain slurry, which is poured into a mold, and the environmentally friendly lightweight building material is obtained after solidification and curing.

[0050] Example 5

[0051] A method for preparing an environmentally friendly lightweight building material is as follows:

[0052] 18 kg of silicate cement, 20 kg of perlite, 20 kg of fly ash, 1.5 kg of aluminum silicate fiber, 0.8 kg of sodium rosin acid, 4 kg of polyvinyl alcohol, 1.5 kg of polyacrylamide, and 50 kg of water are mixed and stirred evenly to obtain slurry, which is poured into a mold, and the environmentally friendly lightweight building material is obtained after solidification and curing.

[0053] Test Example 1

[0054] Test Example 1 Drying shrinkage test was performed on the environmentally friendly lightweight building materials of Examples 1-5, and the test was based on the standard test method of national standard GB / T 23451-2023 "Lightweight partition wall strips for construction". The environmentally friendly lightweight building materials of Examples 1-5 were cut to obtain 400mm×100mm×25mm test pieces, and 3 test pieces were prepared for each example. The test results are summarized in Table 1.

[0055] Table 1 Drying shrinkage test results

[0056]

[0057]

[0058] No fiber material is added to the basic formula of Example 1 of the present invention, and its drying shrinkage value is 0.59 mm / m. Different fiber materials are added to Examples 2-5 on the basis of Example 1. In Example 1 without fiber material, water easily forms a concentration gradient locally during the drying process, which leads to uneven shrinkage. At the same time, water loss during drying is free evaporation, which easily produces large pores and microcracks. In Example 2-5, fiber materials are added to improve the diffusion path of water in the material, making it more uniform, and reducing the shrinkage difference caused by uneven water distribution. In Example 2, wood fiber is added, and the drying shrinkage value is reduced to 0.49 mm / m. Wood fiber forms a three-dimensional network structure in the material, absorbs and retains water during the material drying process, makes the water distribution inside the material more uniform, reduces the drying shrinkage difference caused by uneven water, and can weaken the mechanical energy during the drying process, thereby reducing the drying shrinkage. Wood fiber contains a large number of hydrophilic groups, which can be tightly combined with water molecules through hydrogen bonds. It can slowly release the absorbed water during the material drying process, so that the humidity change inside the material is moderate, and avoids the sharp shrinkage of volume due to the sharp reduction of water. In terms of toughness, wood fiber has high toughness, and its intermolecular force enables it to withstand tensile and deformation stress when the material dries and shrinks, dispersing and bearing stress, and increasing the material's ability to resist deformation.

[0059] Example 3 modified the wood fiber on the basis of Example 2, and the drying shrinkage value was further reduced to 0.47m / m, wherein propylene glycol can form a protective layer on the surface of the wood fiber by impregnation, effectively preventing the loss of carbonate on the surface, and reducing the deformation caused by drying shrinkage; magnesium carbonate and zinc carbonate are attached to the structural gap of the wood fiber for filling, increasing the roughness of the fiber material, so that the modified wood fiber can form a tighter combination when mixed with other materials such as silicate cement and perlite, further optimizing the internal structure of the material, helping to better transfer and disperse stress, and avoiding stress concentration in local areas causing material cracking and shrinkage deformation. Examples 4-5 added sepiolite fiber and aluminum silicate fiber respectively, and the drying shrinkage values ​​were 0.53mm / m and 0.55mm / m respectively. The sepiolite fiber can hinder the generation and expansion of microcracks in the material to a certain extent, reduce the tension caused by drying shrinkage, reduce the material gap, and then reduce the drying shrinkage. The aluminum silicate fiber in Example 5 itself has a low shrinkage rate, and after adding, the overall stability of the material can be improved, which helps to reduce the drying shrinkage value.

[0060] Test Example 2

[0061] The environmentally friendly lightweight building materials of Examples 1-3 were cut into 500mm×400mm×25mm test pieces, and 5 test pieces were prepared for each example. The environmentally friendly lightweight building materials of Examples 1-3 were tested using a thermal conductivity meter to read the thermal conductivity values ​​of the test pieces. The lower the thermal conductivity, the better the thermal insulation performance. The test data were averaged and summarized as shown in Table 2.

[0062] Table 2 Thermal insulation performance test

[0063] Example Example 1 Example 2 Example 3 Thermal conductivity value (W / m·K) 0.1605 0.0921 0.0730

[0064] The difference in thermal insulation performance of the environmentally friendly lightweight building materials of Examples 1-3 lies in whether wood fiber materials are added and whether the wood fiber materials are modified. In Example 1, no fiber material is added, and it is only composed of silicate cement, perlite, fly ash, foaming agent, polyvinyl alcohol, polyacrylamide and water. Its thermal insulation performance is relatively poor. Although perlite has certain thermal insulation performance, the lack of fiber material reduces heat transfer. In Example 2, wood fiber is added, and the thermal conductivity value is reduced to 0.0921W / m·K, and the thermal insulation performance is improved; among them, wood fiber has a small specific gravity and a large specific surface area, and it itself has certain thermal insulation and heat insulation properties, which can form more tiny gaps inside the material. The air plays a good thermal insulation role in these gaps, reducing direct heat conduction between materials. In Example 3, the wood fiber is modified, and the thermal conductivity value reaches 0.0730 W / m·K, and the thermal insulation performance is further enhanced; in the preparation of the modified wood fiber, propylene glycol is used as a solvent and plasticizer, which helps to disperse magnesium carbonate and zinc carbonate in water, and may penetrate into the wood fiber, increase the tortuous path of heat transfer, slow down the heat conduction speed, thereby more effectively preventing heat transfer and further improving the thermal insulation performance.

[0065] Test Example 3

[0066] The environmentally friendly lightweight building materials of Examples 1-5 were tested for impact resistance, and the test was based on the falling ball impact test in the national standard GB / T23451-2023 "Lightweight partition wall strips for construction". The environmentally friendly lightweight building materials of Examples 1-5 were cut to obtain 500mm×400mm×25mm test pieces, and 4 test pieces were prepared for each example. The most severe condition of the 4 test pieces was used as the test result.

[0067] According to the test example 3, the environmentally friendly lightweight building material specimens of Examples 1-5 have no cracks on the board surface after 5 impact tests, and all meet the standards.

[0068] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. An environmentally friendly lightweight building material, characterized in that: The invention comprises the following components in parts by weight: 15-20 parts of silicate cement, 15-25 parts of perlite, 15-25 parts of fly ash, 1-2 parts of fiber material, 0.6-1.0 parts of foaming agent, 2-6 parts of polyvinyl alcohol, 1-2 parts of polyacrylamide and 40-60 parts of water.

2. The environmentally friendly lightweight building material according to claim 1, characterized in that: The fiber material is one of sepiolite fiber, aluminum silicate fiber, wood fiber and modified wood fiber.

3. The environmentally friendly lightweight building material according to claim 2, characterized in that: The preparation method of the modified wood fiber is as follows, in parts by weight: 1.2-1.6 parts of propylene glycol and 0.4-0.8 parts of carbonate are added to 8-12 parts of water, ultrasonically dispersed, citric acid aqueous solution is added dropwise to adjust the pH, 1.2-1.6 parts of wood fiber is added thereto and soaked for 1-2 hours, and the filter cake is filtered and dried to obtain modified wood fiber.

4. The environmentally friendly lightweight building material according to claim 3, characterized in that: The pH is adjusted to 7-8.

5. The environmentally friendly lightweight building material according to claim 3, characterized in that: The carbonate is a mixture of one or more of magnesium carbonate, copper carbonate, calcium carbonate and zinc carbonate.

6. The environmentally friendly lightweight building material according to claim 3, characterized in that: The citric acid aqueous solution is 10-20 wt%.

7. The environmentally friendly lightweight building material according to claim 1, characterized in that: The foaming agent is sodium rosinate.

8. A method for preparing the environmentally friendly lightweight building material according to any one of claims 1 to 7, characterized in that: The preparation method is as follows: Portland cement, perlite, fly ash, fiber material, foaming agent, polyvinyl alcohol, polyacrylamide and water are mixed and stirred evenly to obtain slurry, which is poured into a mold, and the environmentally friendly lightweight building material is obtained after solidification and curing.

Citation Information

Patent Citations

  • Building lightweight material and preparation method thereof

    CN103693900A

Cited By

  • Lightweight building material containing distillers' grains as well as preparation method and application of lightweight building material

    CN121362016A

  • A lightweight building material containing vinasse and a preparation method and application thereof

    CN121362016B